Strategi Eksistensi Salam Rancage sebagai Industri Kreatif Kerajinan Limbah Koran di Bogor - Anisa Febriyani; Mudjiati (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2025)
The creative industry of recycled crafts is growing and innovating as an effort to reduce environmental pollution. One of the creative industries in this field is Salam Rancage. Salam Rancage processes newspaper waste into products of economic value. However, this creative industry faces various challenges, such as market competition and the availability of raw materials. The challenges affects business sustainability and hinder the production process. Therefore, this research aims to analyze the strategies of Salam Rancage in maintaining its existence based on Michael A. Porter's Competitive Strategy theory and the existence of handicrafts produced based on Martono's Craft Aesthetics theory. The research method used is a qualitative approach with descriptive analysis techniques. The results of this study indicate that Salam Rancage has implemented all aspects of Competitive Strategy as follows: (1) Cost Leadership is achieved by utilizing environmentally friendly raw materials sourced from waste banks, (2) Differentiation is achieved by differentiating the materials used in product creation, (3) Innovation is carried out through regular exhibitions and market research, (4) Growth is achieved by organizing sewing and cloth mask-making training to maintain its presence in society, and (5) Alliance is formed through collaborations with the government and the women weavers. Based on the Craft Aesthetics theory analysis, Salam Rancage has applied form follows function, creative coloring, contextual function, and economic efficiency. However, Salam Rancage has not yet applied ornamental aspects to the handicrafts produced.